Diversity and Abundance of Invertebrates Associated with Two Macroalgal Species in the Central Red Sea Coast of Saudi Arabia - Alamer, Sultan; Jamal, Mamdoh; Sathianeson, Satheesh (Journal of King Abdulaziz University: Marine Sciences, 2023)
Studies on the diversity of the macroalgal-associated invertebrates of the Red Sea coast of Saudi Arabia are limited. The diversity and abundance of the invertebrates associated with two morphologically different abundant macroalgal species Acanthophora and Padina north of Jeddah coastal waters on the central Red Sea during the summer and winter seasons were studied. A total of seven major groups belonging to 18 families were observed during this study. The most abundant invertebrate taxa were crustaceans followed by molluscs and polychaetes. In general, the density of epifaunal communities associated with Acanthophora and Padina was higher during summer than winter season. The mean total number of invertebrates associated with Acanthophora was also higher than Padina during the summer and winter seasons. Significant seasonal variations were observed in the abundance of isopods and decapods.